Debris, Roughness and Friction of Stainless Steel Archwires Following Clinical Use - Vieira Marques, Isabella Silva; Araujo, Adriana M.; Gurgel, Júlio de Araújo [UNESP]; Normando, David (E H Angle Education Research Foundation, Inc, 2010)
Objective: To investigate the degree of debris, roughness, and friction of stainless steel orthodontic archwires before and after clinical use.Materials and Methods: For eight individuals, two sets of three brackets (n = 16) each were bonded from the first molar to the first premolar. A passive segment of 0.019- x 0.025-inch stainless steel archwire was inserted into the brackets and tied by elastomeric ligature. Debris level (via scanning electron microscopy), roughness, and frictional force were evaluated as-received and after 8 weeks of intraoral exposure. Mann-Whitney, Wilcoxon signed-rank, and Spearman correlation tests were used for statistical analysis at the .05 level of significance.Results: There were significant increases in the level of debris (P = .0004), roughness of orthodontic wires (P = .002), and friction (P = .0001) after intraoral exposure. Significant positive correlations (P < .05) were observed between these three variables.Conclusion: Stainless steel rectangular wires, when exposed to the intraoral environment for 8 weeks, showed a significant increase in the degree of debris and surface roughness, causing an increase in friction between the wire and bracket during the mechanics of sliding. (Angle Orthod. 2010;80:521-527.)
Keywords: Orthodontic archwire; Roughness; Friction